Effect of zeolite pore morphology on solvent-less alkylation of benzene with 1-hexene. (June 2017) - Saxena, Sandeep K.; Viswanadham, N.; Al-Muhtaseb, Ala'a H.
Abstract: In an attempt to convert the carcinogenic benzene which is almost restricted for its use in gasoline, alkylation reaction with olefin 1-hexene has been conducted on various zeolites. Four zeolites having different pore topology and pore size have been applied as solid acid catalysts for effective production of alkylate in a liquid phase, solvent-less low temperature reaction. The textural properties of all the four zeolites (ZSM-5, MOR, BEA, HY) have been characterized for crystal morphology by TEM, crystal structure by XRD and FTIR, BET for surface area, N2 sorption for porosity and TPD for acidity. Among the zeolite, BEA possessed high surface area (600.61 m 2 /g) and enhanced meso pores volume (0.3956 cm 3 /g) as compared to other zeolite samples. The performance of BEA was also observed to be superior in the liquid phase alkylation of benzene with 1-hexene in a batch reactor under autogenous pressure without using any solvent. At the optimum reaction conditions, the benzene conversion was 86.6 wt% and 3-Phenylhexane, 2-Phenylhexane yield were about 47.9 wt% and 38.7 wt% respectively on this catalyst. The BEA also exhibited longer time-on-stream and reusability performance, thus offers an attractive route for converting benzene into valuable (3-Phenylhexane, 2-Phenylhexane) alkylate product useful for the manufacturing of fine chemicals, dyestuff, detergents and scents. Graphical abstract: Highlights: Higher external surface area and strong acidity was possessed by nano crystalline BEA. Enhanced porosity contributed by mesopores makes BEA better alkylation catalyst. Nano crystalline BEA possesses promising benzene alkylation activity with 1-hexene. Facile diffusion makes the catalyst stable with reaction time and cycles.